Acculturation and Preservation of Islam-Bugis Culture of Makarti Jaya River Basin, South Sumatra - Muhamad Arpah Nurhayat; Maulani Maulani; Muhammad Alfath Qaaf (Khazanah Sosial, 2023)
This paper describes the process of acculturation and the form of preservation of Islam-Bugis culture in Makarti Jaya River in South Sumatra. This research is a type of field research using qualitative methods. The data in this study were obtained through observation, interview, and documentation techniques. This research found four products of Islamic-Bugis cultural acculturation; Maccera` Aqorang (slaughtering animals before reading a letter that is considered auspicious), MappanrÃ© lebbÃ© (a tradition of reciting the Qur'an for prospective brides), cememe mallodung (bathing to remove bad traits before performing the pilgrimage), and Mabbaca Sure` Makkelluna Nabitta (reading the saga of shaving the hair of the Prophet Muhammad Saw). This research succeeded in contributing new treasures in the study of Islamic and Bugis culture, in the multicultural province of South Sumatra. For further researchers, it is recommended to study Islamic-Bugis culture in Makarti Jaya River by using a philological approach, because during the research process the author obtained several ancient texts that were used by the Bugis Makarti Jaya community as a reference in the process of acculturation of Islamic-Bugis culture.